Pengaruh Modal Kerja, Struktur Modal, dan Pertumbuhan Perusahaan terhadap Capaian Laba Bank BUMN Indonesia - Musadat, Irfan Achmad; Puspita, Mugi; Pramayuda, Agung; Ningrum, Retno Widya; Dwiyanto, Bambang Sugeng (Universitas Proklamasi 45, 2025)
This study aims to analyze the effect of working capital, capital structure, and company growth on profit achievement in Indonesian state-owned banks (Bank BUMN). Efficiently managed working capital can enhance liquidity and profitability, while an optimal capital structure plays a role in balancing debt and equity to maximize company value. Additionally, company growth reflects business expansion, which can influence financial performance. This research employs a quantitative method, utilizing secondary data obtained from Bank BUMN's financial statements over a specific period. The analytical technique used is multiple linear regression to determine the relationship between the independent variables and profit achievement. The findings show that working capital significantly affects profit achievement, and capital structure also has a notable impact on profit achievement. In contrast, company growth does not influence profit achievement. These findings have implications for bank management in making decisions related to working capital management, capital structure policies, and growth strategies to enhance profitability.